Clinical and molecular characteristics of lymphoplasmacytic lymphoma not associated with an IgM monoclonal protein: A multicentric study of the Rete Ematologica Lombarda (REL) network. Issue 11 (9th September 2019) - Varettoni, Marzia; Boveri, Emanuela; Zibellini, Silvia; Tedeschi, Alessandra; Candido, Chiara; Ferretti, Virginia Valeria; Rizzo, Ettore; Doni, Elisa; Merli, Michele; Farina, Lucia; Goldaniga, Maria; Gallì, Anna; et al.
Abstract: Lymphoplasmacytic lymphoma (LPL) is usually associated with a serum IgM paraprotein, corresponding to Waldenström's Macroglobulinemia (WM). Cases presenting with IgG or IgA, or without a monoclonal protein are extremely rare. We analyzed clinical characteristics, frontline treatment, and the outcome of 45 patients with non‐IgM LPL, and compared them with a control group of WM patients. The median age was similar, with significantly higher prevalence of females in non‐IgM LPL, than in WM patients (60% vs 39%, P = .016). Patients with non‐IgM LPL more frequently presented with lymphadenopathies (53% vs 15%, P < .001), splenomegaly (22% vs 8%, P = .015) or extranodal involvement (20% vs 8%, P = .05). In non‐IgM LPL a serum monoclonal protein and bone marrow infiltration were less common than in WM patients (69% and 84% of cases respectively, P < .001 for both comparisons). The MYD88 (L265P) mutation was found in 8/19 patients using allele‐specific polymerase chain reaction. A CXCR4 mutation was found in 4/17 cases using Sanger. In 16 patients we performed targeted next‐generation sequencing of genes MYD88, CXCR4, ARID1‐A, KMT2D, NOTCH2, TP53, PRDM1, CD79B, TRAF3, MYBBP1A, TNFAIP3 . Seven patients (44%) had a MYD88 mutation (S219C in one), four (25%) a CXCR4 mutation, three (19%) a KMT2D mutation, one (6%) a TP53 mutation and one (6%) a TRAF3 mutation. With a median follow‐up of 55.7 months, 36 non‐IgM LPL patients (80%) were treated. Non‐IgM LPL patients received more frequently anthracycline‐containing regimens, as compared with WM patients, who mainly received alkylating‐based therapies. Five‐year overall survival (OS) was 84%, similar to that of WM patients.